Respostas
respondido por:
5
Boa noite!!
2x -[5+3(x+8)-11] = 5x
2x -[5 +3x +24 -11] = 5x
2x -[3x +18] = 5x
2x -3x -18 = 5x
5x +x = -18
6x = -18
x = -18/6
x = -3
Bons estudos!
2x -[5+3(x+8)-11] = 5x
2x -[5 +3x +24 -11] = 5x
2x -[3x +18] = 5x
2x -3x -18 = 5x
5x +x = -18
6x = -18
x = -18/6
x = -3
Bons estudos!
maricarvalho201:
Igualmente
respondido por:
1
2x - [5 + 3x + 24 -11] = 5x
2x -5 -3x -24 +11 = 5x
- x - 5x = 29 - 11
-6x = 18
x= -3
2x -5 -3x -24 +11 = 5x
- x - 5x = 29 - 11
-6x = 18
x= -3
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás